A systematic review and meta‐analysis on the effects of transcranial direct current stimulation in depressive episodes. Issue 7 (26th February 2020) - Razza, Lais B.; Palumbo, Priscila; Moffa, Adriano H.; Carvalho, Andre F.; Solmi, Marco; Loo, Colleen K.; Brunoni, Andre Russowsky
Abstract: Background: Transcranial direct current stimulation (tDCS) has shown mixed results for depression treatment. Objective: To perform a systematic review and meta‐analysis of trials using tDCS to improve depressive symptoms. Methods: A systematic review was performed from the first date available to January 06, 2020 in PubMed, EMBASE, Cochrane Library, and additional sources. We included randomized, sham‐controlled clinical trials (RCTs) enrolling participants with an acute depressive episode and compared the efficacy of active versus sham tDCS, including association with other interventions. The primary outcome was the Hedges' g for continuous depression scores; secondary outcomes included odds ratios (ORs) and number needed to treat (NNT) for response, remission, and acceptability. Random effects models were employed. Sources of heterogeneity were explored via metaregression, sensitivity analyses, subgroup analyses, and bias assessment. Results: We included 23 RCTs (25 datasets, 1, 092 participants), most (57%) presenting a low risk of bias. Active tDCS was superior to sham regarding endpoint depression scores ( k  = 25, g  = 0.46, 95% confidence interval [CI]: 0.22–0.70), and also achieved superior response ( k  = 18, 33.3% vs. 16.56%, OR = 2.28 [1.52–3.42], NNT = 6) and remission ( k  = 18, 19.12% vs. 9.78%, OR = 2.12 [1.42–3.16], NNT = 10.7) rates. Moreover, active tDCS was as acceptable as sham. No risk of publication bias was identified. Cumulative meta‐analysis showed that effect sizes are basically unchanged since total sample reached 439 participants. Conclusions: TDCS is modestly effective in treating depressive episodes. Further well‐designed, large‐scale RCTs are warranted.